2018
DOI: 10.5539/jas.v10n2p234
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation’s Complete Protocol of Red Araçá (Psidium cattleianum, Myrtaceae) from Germinated Seeds in vitro

Abstract: Red Araçá's (Psidium cattleianum) micropropagation processes have shown enormous potential both in terms of research and as a sustainable native resource to be used in the areas of food production, ecology, and pharmacology. Currently, however, despite that potential, research efforts involving this myrtaceae, native to the Brazilian Atlantic Forest, have been scarce. With that in mind, this study set out to establish micropropagation techniques that would allow the development of a feasible protocol to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…2 D). This result follows those reported by Freire et al [ 29 ] who mentioned that in Myrtaceae explants a higher concentration of phytohormones could be considered as phytotoxic. In this regard, Rai and his research team [ 30 ] showed that using BA in a concentration of 1 mg/L achieved a high number of buds of P. guajava while increasing the concentration to 2 mg/L induced a sharp decrease in bud formation.…”
Section: Resultssupporting
confidence: 92%
“…2 D). This result follows those reported by Freire et al [ 29 ] who mentioned that in Myrtaceae explants a higher concentration of phytohormones could be considered as phytotoxic. In this regard, Rai and his research team [ 30 ] showed that using BA in a concentration of 1 mg/L achieved a high number of buds of P. guajava while increasing the concentration to 2 mg/L induced a sharp decrease in bud formation.…”
Section: Resultssupporting
confidence: 92%